Complexation of divalent copper, zinc and calcium ions by phosphate esters in aqueous solution - Kramer, Ulrike (Department of Chemistry, 2016)
The role of metal ions as catalysts for numerous biochemical reactions has been the subject of many investigations. One of the most important classes of ligands are phosphate esters. In this thesis I describe the investigation of some phosphate ester-metal ion equilibria. Formation constants for the complexation of p-nitrophenyl phosphate, phenyl phosphate, 1-naphthyl phosphate, α-D-glucose-1'-phosphate, glycerol-2-phosphate, methyl phosphate, 8-quinolyl phosphate, 8-quinolyl methyl phosphate, triphosphate and fluorotriphosphate with protons, copper, zinc and calcium ions were determined by potentiometry. In addition, the complexation of 1-naphthyl phosphate, 8-quinolyl phosphate and 8-quinolyl methyl phosphate with nickel and cobalt ions was also studied. Protonation enthalpies and copper complexation enthalpies of p-nitrophenyl phosphate, phenyl phosphate, 1-naphthyl phosphate, α-D-glucose-1'-phosphate, glycerol-2-phosphate and methyl phosphate were determined by calorimetry. A correlation between the nucleophilicity of the ester group and the magnitude of the stability constants of the proton, copper and zinc complexes of p-nitrophenyl phosphate, phenyl phosphate, 1-naphthyl phosphate, α-D-glucose-1'-phosphate, glycerol-2-phosphate and methyl phosphate is found and explained in terms of electronic induction effects, i.e. by polarisation of the phosphate oxygens by the ester group. The calorimetric results show that the desolvation of ligand and metal ion during the complexation plays an important role. The possibility of similar correlations for complexes of triphosphates is also discussed.